Mycobacterium tuberculosis and whole-genome sequencing: how close are we to unleashing its full potential?. (June 2018) - Satta, G.; Lipman, M.; Smith, G.P.; Arnold, C.; Kon, O.M.; McHugh, T.D.
Abstract: Background: Nearly two decades after completion of the genome sequence of Mycobacterium tuberculosis (MTB), and with the advent of next generation sequencing technologies (NGS), whole-genome sequencing (WGS) has been applied to a wide range of clinical scenarios. Starting in 2017, England is the first country in the world to pioneer its use on a national scale for the diagnosis of tuberculosis, detection of drug resistance, and typing of MTB. Aims: This narrative review critically analyses the current applications of WGS for MTB and explains how close we are to realizing its full potential as a diagnostic, epidemiologic, and research tool. Sources: We searched for reports (both original articles and reviews) published in English up to 31 May 2017, with combinations of the following keywords: whole-genome sequencing, Mycobacterium, and tuberculosis. MEDLINE, Embase, and Scopus were used as search engines. We included articles that covered different aspects of whole-genome sequencing in relation to MTB. Content: This review focuses on three main themes: the role of WGS for the prediction of drug susceptibility, MTB outbreak investigation and genetic diversity, and research applications of NGS. Implications: Many of the original expectations have been accomplished, and we believe that with its unprecedented sensitivity and power, WGS has the potential to address many unanswered questions in the near future. However, caution is still needed when interpreting WGS data as there are some important limitations to be aware of, from correct interpretation of drug susceptibilities to the bioinformatic support needed.